(untitled) (Indian Journal of Child Health, 2014)
Langerhans cell histiocytosis is a rare disorder of unknown etiology with proliferation of Langerhans’ cells which may infiltrate a single or multiple organs. We report a case of 5-year-old child presented with skin lesions since the age of 4 months and fever for 10 days where skin biopsy revealed histiocytosis.